2018
DOI: 10.1186/s40169-018-0210-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination systemic therapies with immune checkpoint inhibitors in pancreatic cancer: overcoming resistance to single‐agent checkpoint blockade

Abstract: Immune checkpoint inhibitors have demonstrated broad single-agent antitumor activity and a favorable safety profile that render them attractive agents to combine with other systemic anticancer therapies. Pancreatic cancer has been fairly resistant to monotherapy blockade of programmed cell death protein 1 receptor, programmed death ligand 1, and cytotoxic T-lymphocyte associated protein 4. However, there is a growing body of preclinical evidence to support the rational combination of checkpoint inhibitors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…Other mechanisms of resistance to immune checkpoint blockade in pancreatic cancer include aberrant expression of immune checkpoints such as PD-L1 on the tumor cell surface, downregulation of antigen presenting MHC molecules, reduced Fas receptor signaling and therefore a reduction in counterattack by T cells via the expression of Fas ligands [64, 65]. In addition, the establishment of a highly desmoplastic TME by stromal cells creates a therapeutic barrier in treating pancreatic cancer [66].…”
Section: Main Textmentioning
confidence: 99%
“…Other mechanisms of resistance to immune checkpoint blockade in pancreatic cancer include aberrant expression of immune checkpoints such as PD-L1 on the tumor cell surface, downregulation of antigen presenting MHC molecules, reduced Fas receptor signaling and therefore a reduction in counterattack by T cells via the expression of Fas ligands [64, 65]. In addition, the establishment of a highly desmoplastic TME by stromal cells creates a therapeutic barrier in treating pancreatic cancer [66].…”
Section: Main Textmentioning
confidence: 99%
“…Further studies should be performed towards combined therapies 87. Combination systemic therapies or radiotherapy with immune checkpoint inhibitors in pancreatic cancer can overcome resistance to single‑agent checkpoint blockade 88. Radiotherapy of pancreatic cancer in older patients is feasible and can be used.…”
Section: Resultsmentioning
confidence: 99%
“…Given the predictive role of PD-L1 overexpression in PDAC was still controversial, our case suggested that PD-L1 overexpression may have the potential to select population. Moreover, emerging evidence supported combining systemic therapy on an ICIs backbone to overcome resistance due to the superior safety of ICIs (15). Theoretically, systemic chemotherapy was regarded as an immunogenic approach by stimulating anti-cancer immune effectors or inhibiting immunosuppressive factors (16).…”
Section: Discussionmentioning
confidence: 99%